Problems of eliminating youth unemployment in Omsk in the 1920s - R. V. Rybakov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of socio-economic methods to overcome youth unemployment in Omsk in the 1920s. Archival materials and regional periodicals are used as the main source base. The publication demonstrates the dependence of the nature of youth unemployment on the specifics of regional industry and analyzes the factors influencing employment dynamics. The author comes to the conclusion that limited material resources and the lack of high demand for qualified specialists made it difficult to solve the problem. At the same time, thanks to the increase in the number of adolescents in the vocational education system, it was possible to stabilize the situation with youth employment and improve their financial situation.